UJI BEBERAPA KONSENTRASI PUPUK CAIR AZOLLA (Azolla pinnata) PADA PERTUMBUHAN BIBIT KELAPA SAWIT (Elaeis guineensis Jacq.) DI PEMBIBITAN UTAMA - Suryati, Dhiya; Anom, Edison; ', Sampurno2 (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The objective of the research was to determine the influence of some Azolla liquid fertilizer concentrations and to get the best concentration on the growth of oil palm seeds in main nursery. Research was carried out in land of Plant Laboratory – Agriculture Faculty University of Riau, from February to May 2014. This research arranged experimentaly using Completely Randomized Design (CRD), consist by 5 treatments and each treatment was repeated 4 times then obtained 20 experimental units. The treatment given was concentration of Azolla liquid fertilizer, consist of: A1 = concentration 50 g/l, A2 = concentration 75 g/l, A3 = concentration 100 g/l, A4 = concentration 125 g/l and A5 = concentration 150 g/l. Parameters measured were the increment of seeds height, increment of leaves number, increment of stump diameter, leaf width, root length, root volume, crown root ratio and seeds dry weight. Data were analyzed statistically using ANOVA and further test followed by Duncan's New Multiple Range Test (DNMRT) at the level of 5%. The results showed that giving some concentration of Azolla liquid fertilizer on growth of oil palm seeds significantly effect on all parameters observed. The best results for the growth of oil palm seeds shown by giving 125 g/l concentration of Azolla liquid fertilizer. Keywords: Azolla liquid fertilizer, oil palm, main nursery